Pengaruh Literasi Keuangan, Inklusi Keuangan, dan Pengelolaan Keuangan Terhadap Kinerja Keuangan Pada UMKM Di Sidoarjo - Rosidah, Herawati; Supardi, Supardi; Kumalasari, Herlinda Maya (Universitas Islam Kadiri, 2025)
This study aims to determine the influence of financial literacy, financial inclusion, and financial management on financial performance in MSMEs in Sidoarjo. This study uses quantitative method techniques. The location of this study is in Sidoarjo Regency. The sample in this study amounted to 100 respondents and the sampling technique used purposive sampling. The analysis technique used in this study is the path analysis technique with the help of application software is SmartPLS software version 4.0. The results of this study indicate that there is a positive influence on the variables of financial literacy, financial inclusion, and financial management on financial performance with the results received in MSMEs in Sidoarjo.